The Dominant Currency Financing Channel of External Adjustment - Camila Casas; Sergii Meleshchuk; Yannick Timmer (Center for Economic Studies and ifo Institute (CESifo), 2023)
We propose a new channel through which exchange rates affect trade. Exploiting the heterogeneity in firms' foreign currency debt maturity structure around a large depreciation in Colombia, we show that debt revaluation compresses imports due to higher delinquencies and interest rates, while exports are unaffected. Natural and financial hedging successfully mute the import contraction. A costly state verification model with dominant currency financing (DCF) and exporting rationalizes these findings. Quantitatively, DCF explains a significant part of external adjustment in addition to the expenditure switching channel. Pricing exports in the dominant vs. producer currency mutes the effect of DCF on trade.
Keywords: F31; F32; F41; G15; G21; G32; 330; imports; exports; foreign currency exposure; capital structure; exchange rates; debt revaluation; hedging